2009
DOI: 10.1007/s00792-009-0239-1
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of thermophilic and hyperthermophilic microorganisms to desiccation

Abstract: We examined short- and long-term desiccation tolerance of 31 strains of thermophilic and hyperthermophilic Archaea and thermophilic phylogenetically deep-branching Bacteria. Seventeen organisms showed a significant high ability to withstand desiccation. The desiccation tolerance turned out to be species-specific and was influenced by several parameters such as storage temperature, pH, substrate or presence of oxygen. All organisms showed a higher survival rate at low storage temperatures (-20 degrees C or belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 62 publications
1
32
0
Order By: Relevance
“…Such a correlation was indeed reported for Halobacterium salinarum NRC-1 (Kish et al 2009), Ustilago maydis (Holloman et al 2007), and bdelloide rotifers (Gladyshev and Meselson 2008). Since a surprisingly high tolerance of vegetative (hyper-) thermophilic Bacteria and Archaea to desiccation could be shown (Beblo et al 2009), in this study the resistance against ionizing and non-ionizing radiation of several (hyper-) thermophilic Bacteria and Archaea was investigated. Main goal was the determination of whether a correlation between desiccation tolerance and radiation resistance could also be found in this group of organisms.…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…Such a correlation was indeed reported for Halobacterium salinarum NRC-1 (Kish et al 2009), Ustilago maydis (Holloman et al 2007), and bdelloide rotifers (Gladyshev and Meselson 2008). Since a surprisingly high tolerance of vegetative (hyper-) thermophilic Bacteria and Archaea to desiccation could be shown (Beblo et al 2009), in this study the resistance against ionizing and non-ionizing radiation of several (hyper-) thermophilic Bacteria and Archaea was investigated. Main goal was the determination of whether a correlation between desiccation tolerance and radiation resistance could also be found in this group of organisms.…”
Section: Introductionmentioning
confidence: 66%
“…The desiccation tolerance of Sulfolobales species is partly influenced by the growth substrate and pH (Beblo et al 2009). As a consequence Metallosphaera sedula, Sulfolobus metallicus and S. solfataricus were exposed to ionizing radiation after cultivation on different growth substrates (ore; elemental sulfur; knallgas) and after neutralization.…”
Section: Ionizing Radiationmentioning
confidence: 98%
See 2 more Smart Citations
“…Detailed resistance studies of vegetative thermophilic and hyperthermophilic Archaea have unexpectedly revealed tolerances against desiccation, vacuum and radiation (UV and g, Beblo et al, 2009). It is unclear however, whether these organisms could cope with the problematic and extremely harsh conditions during space travel, or lack of nutrients and low temperatures in extraterrestrial environments.…”
Section: Discussionmentioning
confidence: 99%